PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE CERAMAH TERHADAP PENGETAHUAN DAN SIKAP PEMBERIAN ASI EKSKLUSIF PADA IBU HAMIL PRIMIGRAVIDA DI PUSKESMAS KAPUAN TAHUN 2016 - Apriliana Apriliana; Kuswanto Kuswanto; Runjati Runjati (JURNAL KEBIDANAN, 2017)
Best nutrition for babies is breast milk which contains a source of nutrition that perfectly suits the needs for growth and development of infants. In exclusive breastfeeding there are some things that hinder the provision of exclusive breastfeeding among mothers is the lack of knowledge, lack of lactation couneling services and support from health, social and cultural factors, lack of adequate conditions for mothers who work and incessant marketing of formula milk.The purpose of this study was to determine the effect of health education with the lecture method to the knowledge and attitudes of exclusive breastfeeding to primigravida pregnant women at health centers Kapuan.This study uses a quantitative research with quasi-experimental method with pre - experimental research design using one-group pretest - posttest design. The study population is primigravida pregnant women at health centers Kapuan with a sampling technique using total sampling with total sample of 46 respondents.The results showed that there was the influence of health education with the lecture method to the level of knowledge and attitude of exclusive breastfeeding to primigravida pregnant women at health centers Kapuan with p-value = 0.001 ( 0.05) and p-value = 0.003 ( 0.05).Suggested pregnant women were able to foster a positive attitude about exclusive breastfeeding through health education to mothers during pregnancy and after childbirth, families and communities.